Generation of β cell-specific human cytotoxic T cells by lentiviral transduction and their survival in immunodeficient human leucocyte antigen-transgenic mice. (16th February 2015) - Babad, J; Mukherjee, G; Follenzi, A; Ali, R; Roep, B O; Shultz, L D; Santamaria, P; Yang, O O; Goldstein, H; Greiner, D L; DiLorenzo, T P
Summary: Several β cell antigens recognized by T cells in the non-obese diabetic (NOD) mouse model of type 1 diabetes (T1D) are also T cell targets in the human disease. While numerous antigen-specific therapies prevent diabetes in NOD mice, successful translation of rodent findings to patients has been difficult. A human leucocyte antigen (HLA)-transgenic mouse model incorporating human β cell-specific T cells might provide a better platform for evaluating antigen-specific therapies. The ability to study such T cells is limited by their low frequency in peripheral blood and the difficulty in obtaining islet-infiltrating T cells from patients. We have worked to overcome this limitation by using lentiviral transduction to 'reprogram' primary human CD8 T cells to express three T cell receptors (TCRs) specific for a peptide derived from the β cell antigen islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP265–273 ) and recognized in the context of the human class I major histocompatibility complex (MHC) molecule HLA-A2. The TCRs bound peptide/MHC multimers with a range of avidities, but all bound with at least 10-fold lower avidity than the anti-viral TCR used for comparison. One exhibited antigenic recognition promiscuity. The β cell-specific human CD8 T cells generated by lentiviral transduction with one of the TCRs released interferon (IFN)-γ in response to antigen and exhibited cytotoxic activity against peptide-pulsed target cells. The cells engrafted in HLA-A2-transgenic NOD- scid IL2rγ null mice and could be detected in the blood, spleen and pancreas up to 5 weeks post-transfer, suggesting the utility of this approach for the evaluation of T cell-modulatory therapies for T1D and other T cell-mediated autoimmune diseases.